Jaminan Hak-hak Perempuan dalam Cerai Gugat Pasca Perceraian: Studi Terhadap Putusan Pengadilan Agama Kota Cimahi - Fitri, Al (Legalita, 2024)
The background of this study is that there are still problems in fulfilling women's rights after divorce, especially default decisions. Even default decisions for imposing obligations on ex-husbands to their wives are relatively minimal and almost ignored. Even if there are any, their implementation could be better because ex-husbands do not fulfil their obligations voluntarily. If executed, the costs incurred are more significant than the husband's obligations imposed in the decision, and there is no interconnection of systems between related institutions. This study aims to determine the considerations of judges at the Cimahi City Religious Court in granting the rights of women in default and to what extent these rights can be fulfilled and their implementation. In answering these problems, the theory used is the mubádalah theory. The study results indicate that a breakthrough is needed so that every divorce decision contains the ex-husband's obligations to the ex-wife as long as it has not been nusyúz. To facilitate its implementation, an interconnection system is needed between institutions that can guarantee the fulfilment of women's rights after divorce as women who are facing the law.